Literacy in everyday life - Blaak, Jeroen,Jackson, Beverley (Brill, 2009)
Preliminary Material /J. Blaak – Chapter One. Historical Research On Reading And Writing: From Book Ownership To The Use Of Media /J. Blaak – Chapter Two. Mirror Of Literacy: Reading And Writing In The Diary (1624) Of David Beck /J. Blaak – Chapter Three. Aristocratic Literacy: Pieter Teding Van Berkhout And His ‘Journal’ (1669–1712) /J. Blaak – Chapter Four. Aural And Eyewitness Testimony: Reading, Writing, And Discussions Of Current Affairs In Jan De Boer’S Chronological Journal (1747–1758) /J. Blaak – Chapter Five. A Devout Reader And Writer: Literacy In Jacoba Van Thiel’S ‘Account-Book Of The Soul’ (1767–1770) /J. Blaak – Chapter Six. Literacy In Everyday Life /J. Blaak – Appendix I. Reading Behaviour In Figures /J. Blaak – Appendix II. Titles Of Books Mentioned In The Diaries /J. Blaak – List Of Sources /J. Blaak – Bibliography /J. Blaak – Index /J. Blaak. Until recently, historians of reading have concentrated on book ownership and trying to map out a history of who read what. The reading experience has been a subject more difficult to research. As has been pointed out before, egodocuments can be valuable sources in this case. Following this lead, Literacy in Everyday Life focuses upon four early modern Dutch diaries in which readers document their daily life and in which they recount their reading. In the analysis, other ways in which these four readers communicated are also addressed, especially speech and writing. This book therefore provides an insight into the possible uses of literacy and the interaction between the printed, written and spoken word in the early modern Dutch Republic
Includes bibliographical references and index
Keywords: Books and reading in literature; Books and reading; Dutch literature; Dutch prose literature; Literacy; Alfabetisme; Dagboeken; Leesgewoonten; Schrijven